Wie die vita contemplativa zur überlegenen vita activa werden kann: Seneca, De otio 6 - Wiener, Claudia (Lucius Annaeus Seneca, 2024)
The basic structure of chapter 6 is formed by several logical conclusions. Seneca uses syllogisms to prove that the otium of the wise is the superior vita activa. Seneca questions seemingly clear ideas of concepts (as vita activa versus vita contemplativa) and thus achieves semantic expansion. Zeno is used as a role model to defend this type of vita contemplativa the Stoic school founders chose even though the recommended political activity. The apparent contradiction of praecepta and practiced way of life is also thematised in De tranquillitate animi. A comparison of the two essays shows that the therapeutic approach in De tranquillitate animi prompts Seneca to make an addressee-related recommendation, while in the discursive essay De otio he examines and confirms or differentiates generally valid statements on the wise man’s right to otium, which can then be applied to his own choice of life.